PENGARUH CUCI TANGAN TERHADAP MUTU MAKANAN DI INSTALASI GIZI RUMAH SAKIT UMUM DAERAH MAJALAYA - Ceria Febiana; Wiwin Windiani (POLITEKNIK PIKSI GANESHA, 2020)
This research was conducted to find out how the influence of hand washing on food quality in nutrition installations at Rumah Sakit Umum Daerah Majalaya. The research method used in this research is a quantitative method with a descriptive approach, the data collection techniques used are by observation, questionnaire and literature study. Data analysis techniques used validity test, reliability test, sperman rank correlation coefficient and determination correlation coefficient. The results showed that the relationship of hand washing with food quality was at 0.96 or very strong relationship. the results of the analysis of the effect of with hand washing with food quality amounted to 92.16%, thus there are still other variables that affect food quality that is 7.84% From the research of that paper, theres a problems such as: (1) lack of with the proper hand washing rules, (2) the use of personal protective equipment (3) lack of labor in the nutrition installation so that an employee must carry out two jobs. The conclution to that problem are (1) increasing the supervision of hand washing (2) paying more attention to the human resources in the nutrition installation by adding several staff so that the food service process can be carried out effectively